2018
DOI: 10.1111/eth.12815
|View full text |Cite
|
Sign up to set email alerts
|

On the neglected behavioural variation among neighbouring primate groups

Abstract: Behavioural variation in primates has been well studied at the level of individuals by behavioural ecologists, and more recently at a population level by cultural biologists. Behavioural differences between groups of the same population, however, have rarely been considered. Here, I review intergroup variation in universally occurring behaviours between up to six neighbouring groups of vervet monkeys. Group differences have been found in several domains including foraging, conflicts, grooming and proximity. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 54 publications
(87 reference statements)
2
20
0
Order By: Relevance
“…Overall, these analyses provide evidence that social transmission was option specific, i.e., observing lift increased the rate at which observers learned to solve the task using the lift option, and likewise for the pull option (see Table 2 for estimates of effect sizes and total support for each network). This suggests, confirming previous studies 25,26,44,45 that vervet monkeys demonstrate social transmission that could lead to foraging group-level traditions. However, we also found that once an individual had solved the task using one option it became an estimated 31x more likely to asocially learn the other technique than individuals naive to both techniques (95% CI = 11.3-110.6, support = 100.0%, Table 2, see section "Testing whether the learning generalization effect operated on asocial or social learning" In Supplementary Note 2).…”
Section: Wild Vervet Monkeys Socially Learn a Novel Foraging Techniquesupporting
confidence: 90%
“…Overall, these analyses provide evidence that social transmission was option specific, i.e., observing lift increased the rate at which observers learned to solve the task using the lift option, and likewise for the pull option (see Table 2 for estimates of effect sizes and total support for each network). This suggests, confirming previous studies 25,26,44,45 that vervet monkeys demonstrate social transmission that could lead to foraging group-level traditions. However, we also found that once an individual had solved the task using one option it became an estimated 31x more likely to asocially learn the other technique than individuals naive to both techniques (95% CI = 11.3-110.6, support = 100.0%, Table 2, see section "Testing whether the learning generalization effect operated on asocial or social learning" In Supplementary Note 2).…”
Section: Wild Vervet Monkeys Socially Learn a Novel Foraging Techniquesupporting
confidence: 90%
“…However, to distinguish whether social processes contribute to the emergence of behavioural phenotypes, it is essential to quantify ecological variation and account for its influence on behaviour expression, a challenging endeavour in wild settings. Few studies have attempted to limit potential ecological confounders by investigating behavioural diversity between neighbouring groups ( Luncz and Boesch, 2014 ; Pascual-Garrido, 2019 ; van de Waal, 2018 ). Nonetheless, in the absence of between-group range overlap, fine-scale ecological variation specific to the locations where behavioural phenotypes are expressed cannot be excluded.…”
Section: Introductionmentioning
confidence: 99%
“…The same may be true for troops within the same population that occupy habitats with differential availability, distribution and quality of resources (e.g. Bronikowski & Altmann, , van de Waal, ). Thus, regardless of the intensity or duration of research, studies with small sample sizes are unable to assess the effects of local habitat differences, or take into account individual differences among troops (Isbell & Young, ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies with large sample sizes of troops (e.g. Bronikowski & Altmann, ; van de Waal, ) or complete populations (e.g. Hamilton, Buskirk & Buskirk, ; Iwamoto, ; Takasaki, ) are rare.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation